TEACHER’S STRATEGIES IN TEACHING READING COMPREHENSION PROCEDURE TEXT - Candra Tri Aswuri and Johan Sinulingga (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2017)
This study attempts to investigate the phenomenon which occurred in classroom setting dealing with teacher’s strategies in teaching reading. It was designed in descriptive qualitative research. The location of this study was MTs Al-Jam’iyatul Washliyah Tembung and the samples were the English teacher and the students of IX-4 class who were selected by using random sampling technique. The data of this study deals with kinds of teacher’s strategies in teaching reading procedure text. The data were collected from the observation which occurred during the reading procedure text class and the interview with the English teacher. The data were analyzed by three stages : 1) familiarizing and organizing, 2) coding and reducing, and 3) interpreting and representing. From the data analysis and the data verification, it was obtained that the teacher used three strategies in teaching reading comprehension procedure text, namely activating background knowledge strategy, visualizing strategy, and questioning strategy. The strategies not only were beneficial to promote and improve students’ comprehension but also they encouraged the students to be active, enthusiastic, and critical readers.